Analysis of the symptom response to esomeprazole 20 mg over days 1–4 of a 14-day course of treatment for frequent heartburn: results of two randomised controlled trials. Issue 1 (21st June 2019) - Peura, David; Le Moigne, Anne; Wassel, Heather; Pollack, Charles
Abstract : Background: Drug exposure and corresponding antisecretory effects increase over the first 4–5 days of esomeprazole treatment. To date, this effect has not been correlated with symptomatic improvement. Therefore, the efficacy of esomeprazole was evaluated on days 1–4 and 5–14 using pooled data from two identical randomised, double-blind, placebo-controlled studies conducted in subjects with frequent heartburn who are likely to self-treat with over-the-counter medications. Methods: Adults without confirmed diagnoses of gastro-oesophageal reflux disease experiencing heartburn 2 or more days per week in the past 4 weeks were randomly assigned to treatment with esomeprazole 20 mg or placebo once daily for 14 days following a 1-week placebo run-in period (esomeprazole: n=330; placebo: n=321). Heartburn episodes were documented in daily diaries. The current analyses evaluated the change in baseline percentage of heartburn-free days across days 1–4 and 5–14. Results: Change in the percentage of heartburn-free days from the run-in was significantly greater with esomeprazole compared with placebo (p<0.001) starting on days 1–4. The greatest treatment benefit was observed during days 5–14. During this period, esomeprazole-treated subjects increased their heartburn-free time over the run-in period by 32.5% compared with 14.3% with placebo (p<0.001). Conclusions: Frequent heartburn sufferers treated with esomeprazole 20 mg had significantly more heartburn-free days relative to placebo throughout the studies. Maximal clinical benefits coincided with the estimated timing of maximal pharmacokinetic and pharmacodynamic effects and duration of acid control on days 5–14. Trial registration number: NCT01370525 ; NCT01370538